Proses Perencanaan Anggaran pada Usaha Kuliner “Seblak” - Aziz Fajar Saputro; Redika Fajar Cahyono; Farhan As Sidiq; Rizal Fakihan; Muhammad Aditya Juliyanto (Jurnal Manajemen Bisnis Era Digital, 2026)
A company budget is a structured and logical plan. In business management, a budget serves as a planning, control, and decision-making tool, enabling the company to achieve effective and efficient goals. Furthermore, a company budget aims to regulate cash flow, preventing waste. This article discusses the budgeting process in the culinary business "Seblak" and the importance of proper budgeting for culinary businesses. Budgeting enables companies to effectively manage their businesses and achieve their financial goals. Seblak is a traditional Indonesian dish originating from West Java, particularly the Bandung area. Initially, seblak was a simple dish made from raw crackers, boiled until soft, mixed with spices, and topped with various toppings such as sausage, chicken, and frozen food. Seblak is derived from the word "segak" and "nyegak," two Sundanese words meaning "pungent" or "invigorating." The name is quite synonymous with seblak, which is characterized by its spicy flavor and the use of galangal (galangal) for its strong aroma.